The Effect Of Brand Equity, Marketing Mix, And Lifestyle To Purchase Decision At Maxx Coffee, Bogor - Khairunnisa Rahmah; Ujang Sumarwan; Mukhammad Najib (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2018)
Coffee becomes one of the important commodities both in terms of consumption and in terms of production. Therefore, the interaction in marketing with the system and its activities should be able to get closer between consumers to products and brand name of the company offered. Nowdays, urban society at this time experiencing lifestyle changes. One of the manifestations of modern lifestyle today is the habit of certain community groups who like to consume coffee in coffee shops. Base on that, the purpose of this research is to identify the characteristics of MAXX Coffee consumer, analyze the influence of brand equity, lifestyle, and marketing mix of MAXX Coffee to consumer purchase decision, and to formulate alternative marketing strategy based on factors influencing marketing mix and brand equity MAXX Coffee. This research using Structural equation Modeling (SEM) with 271 respondent based on convenience sampling method during the reseach time. Based on the results of the research, in order to create strong brand equity, the management of MAXX Coffee Bogor can invest through the improvement of several marketing mix indicators, namely price, people, process, and physical. In the context of MAXX Coffee lifestyle focus to follow the perception of today's consumer lifestyle that wants to improve the prestige and image in the environment around consumers.